Thermo-sensitive hydrogel combined with SHH expressed RMSCs for rat spinal cord regeneration - Gu, Jun; Gao, Biao; Zafar, Hajra; Chu, Bo; Feng, Xiaojun; Ni, Yinjie; Xu, Lin; Bao, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Spinal cord injury (SCI) has a damaging impact on patients, amid being a worldwide problem with no effective treatment. Herein, we reported a method for functional therapy of SCI in rats, wherein we combined thermo-sensitive hydrogel with Sonic Hedgehog (SHH) expressed in rat bone-marrow derived mesenchymal stem cells (RMSCs). Methods: Bone marrow-derived mesenchymal stem cells (BMSCs) were isolated from Sprague-Dawley (SD) female rats. The SHH was optimized and transferred into RMSCs via cationic liposomes, while thermo-sensitive hydrogel was reformed with hyaluronate (HA) and Pluronic F127. Then, a rat model with SCI was established accordingly by male SD rats and randomized into sham, model, RMSCs with hydrogel and SHH-RMSCs with hydrogel. The evaluation of SCI repair based on Basso, Beattie Bresnahanlocomotor rating scale (BBB scale) and inclined plate score. Immunofluorescence, immunohistochemistry and hematoxylin-eosin were utilized to explore the expression of protein (GFAP, GAP43, NF200 and MBP) and histopathology. Results: It was demonstrated that transfection of SHH with cationic liposomes exhibited more effect in RMSCs than lipofectamine 2000. As shown in SEM, 3.5% HA-F127 demonstrated porous structure. In the MTT and dead/live assay, 3.5% HA-F127 showed good biocompatibility for RMSCs. Both RMSCs and SHH-RMSCs groups could significantly promote BBB and inclined plate scores (p < 0.01) compared with the model. Furthermore, the SHH-RMSC group was significantly improved than RMSC with the expression of related proteins, where NF200, MBP, and GAP43 were principally enhanced with the GFAP expression being virtually down-regulated. Conclusion: All in all, the results suggested that transplantation of RMSCs with SHH could improve the function of SCI and promote nerve regeneration.